If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 80x + 60(420 + -1x) = 31100 80x + (420 * 60 + -1x * 60) = 31100 80x + (25200 + -60x) = 31100 Reorder the terms: 25200 + 80x + -60x = 31100 Combine like terms: 80x + -60x = 20x 25200 + 20x = 31100 Solving 25200 + 20x = 31100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25200' to each side of the equation. 25200 + -25200 + 20x = 31100 + -25200 Combine like terms: 25200 + -25200 = 0 0 + 20x = 31100 + -25200 20x = 31100 + -25200 Combine like terms: 31100 + -25200 = 5900 20x = 5900 Divide each side by '20'. x = 295 Simplifying x = 295
| 5(w-5)-8w=-1 | | 10x+x^2+25=0 | | 22x^2+40x=80 | | -4x+(1+2x)=-1 | | n/80=5/100 | | log^36x=5/2 | | 2(-1-3y)+2y=6 | | 5s(8s-5)(5s-1)=0 | | 4x+2(1-2x)=-1 | | (0.2x-0.3)(0.04x+3)=0 | | 9s^2+3s-20=0 | | p/d-c/d=1 | | 2y=x^2+3 | | 2x+95=6x+195 | | 2x+120-10x=-6x-20 | | -15+9m= | | 2(3n-1)=(9n+6)+4 | | 3/2|2x-5|-2=7 | | 21r^2+22r-8=0 | | 6y^2-9y+7=0 | | -4(t-2)+9t=3t-5 | | 0.18(y-9)+0.04y=0.12y-0.03(40) | | C=30(3.14) | | (4x+3)(2x-6)= | | 4t^2-40t+25=0 | | 3y=x^2+7 | | -2(1)+8=2 | | 4t^2-40+25=0 | | 0.2x=2.6x-2.8 | | Y=1/3(90-X)-6 | | Y=24-X/3 | | 10-4(3x+1)-(3x-4)= |